The influence of obesity on IOS parameters in asthma, COPD, and other lung diseases: analyzed by random forest - Thomas Ringbaek; Lars Froelund; Jann Mortensen; Henrik H. El Ali (BMC Pulmonary Medicine)
Abstract Background This study investigates the impact of obesity on impulse oscillometry (IOS) parameters in individuals with asthma, chronic obstructive pulmonary disease (COPD), other lung diseases, and non-respiratory conditions. With rising obesity rates, understanding its effects on respiratory health is increasingly essential. We aimed to evaluate IOS parameters as predictors of respiratory dysfunction across different BMI categories, offering insights into managing complex cases involving obesity and lung disease. Methods We retrospectively analyzed IOS data from 1,947 patients referred to a secondary care allergy and lung clinic. IOS parameters assessed included total and peripheral airway resistance (R5 and R5-20), resonant frequency (Fres), and reactance area (AX), examined relative to BMI. The cohort included patients with asthma, COPD, other lung diseases, and controls. A weighted random forest model was used to assess the impact of IOS parameters on BMI prediction accuracy, adjusting for imbalances in BMI and disease groups. Results Obesity significantly affected IOS parameters, with R5-20, AX, and Fres emerging as key markers across all diagnostic groups. Elevated R5-20, AX and Fres values in obese patients, regardless of lung disease status, indicated increased small airway resistance and dysfunction. These IOS features demonstrated high predictive value in BMI-related outcomes, suggesting they capture airway impairments tied to obesity beyond conventional respiratory diagnoses. Conclusions IOS parameters, particularly R5-20, AX, and Fres are sensitive to obesity-associated airway changes and may serve as valuable markers for identifying respiratory impairment in obese individuals with or without lung disease.